Factors associated with survival and lost to follow-up of cervical cancer patients in a tertiary cancer centre in rural Kerala - T Bindu; Saina Sunil Kumar; K Ratheesan; Satheesan Balasubramanian (Wolters Kluwer Medknow Publications, 2017)
Cancer cervix is the second common cause of cancer death in India. It is the most curable form of any human cancer if detected at the precancerous stage. Although several factors determine the survival of the disease, the clinical stage at presentation is the single most important predictor of long-term survival. The present study aimed to describe the performance and follow-up status and 5-year survival experience of the cervical cancer patients registered between 2010 and 2011 by the hospital registry of Malabar Cancer Centre, Kerala, and factors affecting lost to follow-up and survival among them. The case sheets of 227 patients retrospectively scrutinized during May-July 2014. The mean age of patients was 58.8 years (standard deviation = 11.67 years). The majority of the patients completed the initially planned treatment, but a low proportion of patients were likely to be on regular follow-up. This study revealed that most of the patients registered at the hospital only at an advanced stage. Using Kaplan-Meier method, the estimated 5 years survival rate was found to be 66.8%. It was noted that performance status before treatment and Federation of Gynecology and Obstetrics staging were significantly associated with lost to follow-up and survival rate majority of the cervical cancer patients are observed to be highly noncomplaint to complete treatment and on follow-up. Thus, these findings stress the importance of counseling family members regarding the importance of follow-up and formulating public health policies aimed at increasing the awareness and implementation of cervical cancer screening programs in North Malabar.